Cardiorespiratory reflexes in white sturgeon (Acipenser transmontanus): Lack of cardiac baroreflex response to blood pressure manipulation? - Braga, Victor Hugo da Silva [UNESP]; Armelin, Vinicius Araújo; Noll, Igor Guagnoni [UNESP]; Florindo, Luiz Henrique [UNESP]; Milsom, William Kenneth (Elsevier, 2024)
Arterial pressure (Pa) regulation is essential to adequately distribute nutrients to metabolizing tissues, remove wastes and avoid lesions associated with hypertension. In vertebrates, short-term Pa regulation is achieved through the baroreflex, which elicits inversely proportional changes in heart rate (fH) and vascular resistance to restore Pa. The cardiac limb of this reflex has been reported in all vertebrate groups studied to date: teleosts, amphibians, snakes, lizards, crocodiles, birds and mammals – which led to the suggestion that the baroreflex is an ancient trait present in all vertebrate species. However, it is not clear whether more basal groups of vertebrates, such as cyclostomes, elasmobranchs and chondrosteans, manifest baroreflex regulation of fH. Thus, the aim of this study was to determine whether the white sturgeon (Acipenser transmontanus; Chondrostei: Acipenseridae) exhibits a cardiac baroreflex. To do so, we induced Pa perturbations through injections of phenylephrine, sodium nitroprusside (SNP) and saline solution (hypervolemia), and examined possible fH baroreflex responses. We also investigated whether fH responses triggered by fright and chemoreflex were present in this species, in order to confirm the potential of sturgeon to perform reflexive cardiac adjustments. The findings indicate that A. transmontanus exhibits reflex bradycardia in response to fright and chemoreceptor stimulation, illustrating its capacity for short-term cardiac regulation. However, this species does not display baroreflex control of fH across its physiological range. This dissociation suggests that while the nervous and cardiovascular systems of A. transmontanus are primed for rapid reflex responses, a cardiac baroreflex mechanism remains absent.
Keywords: Blood pressure; Heart rate control; Short-term regulation; Vagus nerve